Spatially resolved spectroscopy across stellar surfaces: II. high-resolution spectra across HD 209458 (G0 V) - Dravins, Dainis; Ludwig, Hans-Günter (Astronomy and astrophysics, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics